“Not so much perdition as an hair”: The Political Deployment of Christian Patience in The Tempest - Kasa, Deni (Renaissance and Reformation / Renaissance et Réforme, 2020)
Early modern theology and martyrology understood patience as a transformation of one’s perspective on suffering, so that pain and humiliation came to be seen by the sufferer as honourable and even desirable. This article suggests that The Tempest explores the political implications of Christian patience when the concept is translated to the secular spheres of courtship and politics. Miranda and Ferdinand find a sense of agency through Christian patience, leading to the fulfillment of Prospero’s political goals and the dynastic union that concludes the play. However, the repressive side of Christian patience is also revealed through the play’s exclusion of Caliban.